Memahami Surat Al-Lahab (Studi Tafsir Tematik Surat al-Lahab) - Asyhad Abdillah Rosyid (Menara Tebuireng, 2017)
Qur’an is the direct Islamic guide to stand on, people’s obeydience to understand it as well as, but many people aren’t. Whereas, they read and memorize it, but it quality and quantity aren't balancing. Here it to realise and be wistful it over. al-Lahab is one of the shortest verses in Qur'an which is significant content on people's social and religion's way. Is to show a man and woman images who opposes God and His Prophet will get destruction's revenge as Abu Lahab got. World destruction's and hereafter's one. Firstly isn't coming with continuation ill to his death and nor of sons and family serves his corpse. Secondly will put into the hell with his lovely wife, Umm Jami>l. Other content is center for verse figure not only Prophet's uncle but also as father of Muhammad's daughter. His name is recorded in Quranic special verse, al-Lahab, why? wheres, some Quraisy figures are harder to oppose and sadister to torture Prophet Muhammad, as hard as Abu Jahal, but he hasn't a quranic special verse. Thematic interpretation method will explain as comprehens as it's name, reason's descend, descend's periodic, main topic, relevance, goal and verse's intrepretation